CO2 flow in saline aquifer with salt precipitation - Pau, J.S. (Emerald Group Publishing Ltd., 2016)
Purpose - The purpose of this paper is to introduce the solution to two-phase flow in CO2/brine system with salt precipitation by applying mixed hybrid finite element (MHFE) method to pressure equation and finite volume (FV) method to saturation equation. Mixed finite element method solves pressure and velocity in two subspaces while hybrid method is an extension of mixed method, where the Lagrange multiplier is added to the former in order to ensure the continuity from one element to the adjacent elements. The authors propose the modeling of salt precipitation using core flood experimental result and adapt to be applicable for numerical modeling. Design/methodology/approach - The governing equations are discretized using Mixed Hybrid Finite Element-Finite Volume (MHFE-FV) method. This method has the feature of localized conservation which is attractive for application on heterogeneous porous media. In addition to this, the salt precipitation effect is modeled using the data from core flood experiment (Ott et al., 2011). The random data are linearized to obtain the relationship between salt precipitate and CO2 saturation and implemented to the algorithm for two-phase flow in CO2 and brine system. Findings - The solution of MHFE-FV scheme has good agreement with the solution using implicit pressure and explicit saturation (IMPES) reported by Negara et al. (2011), with average error of 4.20 percent. Localized conservation is demonstrated in the case of randomized heterogeneous porous media where fingering effects are explicitly observed. Salt precipitation prediction using the proposed method is able to predict the decrement of porosity by 16.71 percent and permeability by 22.19 percent. This results in the decreased amount of CO2 injected by 64.70 percent. Research limitations/implications - This paper presents the solution of two-phase flow in CO2 brine system during CO2 injection in saline aquifer using MHFE-FV method with the additional salt precipitation model obtained based on core flood experiment result. Practical implications - A methodology to predict the salt precipitation based on CO2 saturation. Social implications - Contribution to green house gas reduction. Originality/value - The authors use MHFE-FV to solve hyperbolic PDE to obtain accurate results of CO2 saturation, and subsequently use this to compute the salt precipitation. Â© Emerald Group Publishing Limited.